THE INFLUENCE OF DEFICIT EVAPOTRANSPIRATION TOWARD PLANTS GROWTH AND WATER USE EFFICIENCY OF THREE SOYBEAN VARIETIES (Glycine max (L.) Merril) - Febriana Nivoliya (The University of Lampung, 2014)
The objective of this research is to find out the influence of evapotranspiration deficit toward plants growth andwater use efficiency of three soybean varieties (Glycine max. (L) Merr.). This research was conducted in thegreenhouse, integrated laboratory of Agriculture Faculty, Lampung University on November, 2013 to January,2014. This research used a complity randomized design consisting two treatment factors with three timesrepetition. The fisrt factor was evapotranspiration deficit (E) consisting of E1 (1.0), E2 (0.8), and E3 (0.6), andE4 (0.4). The second factorwas variety (V) consisting of Tanggamus (V1), Kaba (V2), andWillis (V3). The resultof research showedthat evapotranspiration deficit and varietywas significantly differentwhereas the interactionwas not significantly different at all growth components, production andwater use efficiency .The highest resultproductionwasWiliis (V3) and Kaba (V2) on E1 (1.0) 12.33 gr/pot. The highest value ofwater use efficiencywasWillis (V3).